A Combined Variable Step Size Strategy for Two Microphones Acoustic Feedback Cancellation using Proportionate Algorithms - Albu, F.; Tran, Linh Thi Thuc; Nordholm, Sven (2017)
This paper proposes to use a combination of the improved proportionate normalized least mean square (IPNLMS) algorithm and a new algorithm called combined-stepsize IPNLMS (CSS-IPNLMS) algorithm in the two microphone closed-loop feedback cancellation technique. The simulation results indicate an improvement in convergence speed of the proposed algorithms as compared to previously suggested methods, especially for the case of the normal feedback path.